Suzuki–Miyaura Cross-Coupling Reaction with Potassium Aryltrifluoroborate in Pure Water Using Recyclable Nanoparticle Catalyst - Kawase, Misa; Matsuoka, Kyosuke; Shinagawa, Tsutomu; Hamasaka, Go; Uozumi, Yasuhiro; Shimomura, Osamu; Ohtaka, Atsushi (Synlett, 2021)
This paper describes the Suzuki–Miyaura cross-coupling reaction of aryl bromides with potassium aryltrifluoroborates in water catalyzed by linear polystyrene-stabilized PdO nanoparticles (PS-PdONPs). The reaction of aryl bromides having electron-withdrawing groups or electron-donating groups took place smoothly to give the corresponding coupling product in high yields. The catalyst recycles five times without significant loss of catalytic activity although a little bit increase in size of PdNPs was observed after the reaction.
Keywords: Suzuki–Miyaura cross-coupling; potassium aryltrifuoroborate; nanoparticles; water; recycling